2002
DOI: 10.1016/s0006-3495(02)75271-5
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid 25 to 35 Is Intercalated in Anionic and Zwitterionic Lipid Membranes to Different Extents

Abstract: Neuronal plasma membranes are thought to be the primary target of the neurotoxic beta-amyloid peptides (Abeta) in the pathogenesis of the Alzheimer's disease. Histologically, Abeta peptides are observed as extracellular macroscopic senile plaques, and most biophysical techniques have indicated the presence of Abeta close to the lipid headgroup region but not in the core of the membrane bilayers. The focus of this study is an investigation of the interaction between Abeta and lipid bilayers from a structural po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
95
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 26 publications
19
95
0
Order By: Relevance
“…Our results are in agreement with the study of Terzi et al (1997) and are in partial agreement with Dante et al [49]. In that case, Ab (28)(29)(30)(31)(32)(33)(34)(35) bound electrostatically to the negatively charged membrane only under physiological conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with the study of Terzi et al (1997) and are in partial agreement with Dante et al [49]. In that case, Ab (28)(29)(30)(31)(32)(33)(34)(35) bound electrostatically to the negatively charged membrane only under physiological conditions.…”
Section: Discussionsupporting
confidence: 94%
“…While oligomerization does occur naturally in solution, there are other possible factors that may catalyze this reaction. Recent work [5][6][7][8][9][10][11][12][13][14][15][16] has demonstrated that cell membranes may play a significant catalytic role in increasing A aggregation rates. The A peptide is derived from the transmembrane amyloid precursor protein (APP).…”
Section: Introductionmentioning
confidence: 99%
“…9 In our previous investigations, we had applied neutron diffraction and selective deuteration to localize the short peptide Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), a toxic fragment of Aβ, into lipid bilayers of different surface charge and composition. [10][11][12] In the present study, the interaction of the most abundant Aβ in senile plaques, that is, Aβ , with unilamellar lipid vesicles (ULVs) is investigated by small-angle neutron scattering (SANS). SANS is a well-established technique for the investigation of lipid vesicles 13 and the change of the parameters describing their structure in different conditions.…”
Section: Introductionmentioning
confidence: 99%